Comparison of the Epidemiological Aspects of Imported Dengue Cases between Korea and Japan, 2006–2010 - Jeong, Young Eui (Osong Public Health Res Perspect, 2016)
To compare the epidemiological characteristics of dengue cases imported by travelers or immigration in both Korea and Japan, we determined dengue incidence and related risk factors. During 2006–2010, 367 and 589 imported dengue cases were reported in Korea and Japan, respectively. In Korea, the presumptive origins for the dengue infections were Southeast Asia (82.6%), Southern Asia (13.9%), Eastern Asia (1.1%), South America (0.3%), Central America (0.3%), Africa (0.3%), and other countries (1.6%). In Japan, the origins of the infections were Southeast Asia (69.8%), Southern Asia (20.0%), Eastern Asia (1.7%), South America (2.5%), Central America (1.2%), Africa (1.2%), Oceania (2.4%), and other countries (1.2%). In both countries, more dengue cases were reported for men than for women (p < 0.01), and those aged 20–30 years accounted for > 60% of the total cases. The frequency of imported cases in summer and autumn (∼70% of total cases) was similar in both countries. This study demonstrates that there is a similar pattern of imported dengue cases in Korea and Japan. Therefore, there is a risk of an autochthonous dengue outbreak in Korea, as indicated by the recent outbreak in Japan in 2014.